Evaluation of dispatch outcomes and staffing of the Copenhagen mobile health and social care unit – Sociolancen - Østergaard, Simon; Lyngby, Rasmus (Dansk Tidsskrift for Akutmedicin, 2019)
Background: The mobile health and social care unit – Sociolancen (MHSCU) is a specialized unit within the Emergency Medical Services (EMS) of the Capital Region of Denmark. The unit provides acute social care for homeless and social deprived groups and is staffed with a social worker and a paramedic and available through the EMS dispatch during daytime. The MHSCU is dispatched to citizens where the need for acute social care is suspected, falling outside the normal scope of practice for emergency ambulances. The aim of this study was to evaluate the dispatch outcomes of the MHSCU and the constellation of paramedical and social effort. Methods: Data on the total number of MHSCU dispatches and outcomes in 2016 and 2017 was retrieved from the dispatch system operated by EMS Copenhagen. Outcome data was grouped for descriptive statistics. Results: During the data collection period the MHSCU was dispatched 2976 times. The outcome resulted in 384 (12.9%) citizens being brought to a somatic emergency department (ED) and 255 (8.6%) citizens being brought to a psychiatric ED. A total of 355 (11.9%) citizens were left to selfcare and 196 (6.6%) citizens were brought to a shelter. Number of citizens handed over from emergency ambulances was 41 (1.4%), number of citizens handed over to emergency ambulances was 4 (0.1%), number of citizens handed over to police was 13 (0.4%). In 1386 (46.6%) cases MHSCU were doing outreach work, citizen had left scene or MHSCU was cancelled. Number of dispatches labeled ‘unknown’ was 342 (11.5%). Conclusions: The outcome of MHSCU dispatches indicate the need for both paramedical and social staffing when attending the homeless and social deprived citizens, as there is an approximately even distribution between health related and social related referral. Half of dispatches covers outreach work not within the normal scope of practice for emergency ambulances, enabling MHSCU to provide community service and security. Further, based on the low referral to emergency ambulances and police, the dispatch of MHSCU seems well-prioritized. Acknowledgments: The authors wish to thank Paramedic Martin Betzer for assistance.